The Relationship Between Artificial Intelligence (AI) Usage and Academic Performance of Business Administration Students - Jaysone Christopher M. Bancoro (PT FORMOSA CENDEKIA GLOBAL, 2024)
Abstract – Artificial Intelligence, renowned for its data interpretation, learning, and task achievement capabilities, has gained popularity in various industries and academies due to enhanced efficiency and quality. This study aims to determine the extent of AI usage among students, including functionality, availability, complexity, assessment scores, course mastery, and grading metrics. It also seeks to determine if a relationship exists between AI usage and their academic performance. The study employs a quantitative approach using a correlational design. The respondents of the study are 293 Business Administration students from Negros Oriental State University Main Campus 1, Dumaguete City. The study's findings suggest that AI usage among students is moderately prevalent in terms of functionality, availability, and complexity. However, the students' academic performance was found to be above-average, with high scores on assessments, course mastery, and excellent grades. There is no significant relationship between AI use and academic performance found. In conclusion, AI tools offer personalized learning experiences, immediate feedback, and collaborative activities, but further growth and improvement are needed, including training, accessibility, research, monitoring, and best practices sharing